Treatment of Pilonidal Sinus by Limberg Flap-Only Hope of Cure (Study of 50 Cases) (Journal of Surgical Sciences, 2020)
Background : Pilonidal sinus was first described by Dr. A.W. Anderson in 1847 and is often seen in the intergluteal region. It is a disease of mainly younger male and rarely affects after 40. Main causes for the formation of this sinus are hirsutism, sweating in the area, repeated maceration due to trauma, leading to breakage of the skin barrier, attracting hair inside which initiates a foreign body reaction leading to infection with abscess or sinus formation. Most common embarrassing situation is discharging sinus. The diagnosis is mainly on clinical ground. Though there are a lot of modalities of treatment but recurrence is still a challenge. We have adopted Limberg flap technique since 2012 with a least recurrent chance.Objectives : To prove that this procedure will be end up with lower morbidity & least chance of recurrenceMethods : This prospective study was done jointly by the Department of Surgery of Central Medical College and Comilla Medical College Hospital. In this series 50 patients were selected from July 2012 to June 2017.Results : Out of 50 patients operated by Limberg flap technique 42(84%) were males and 8(16%) were females. Mean age was 27.3 years (range 18–37years). Of them,12(24%) were driver, 6(12%) police, 6(12%) teacher, 6(12%) student, 5(10%) worker, 4(8%) millitary army, 4(8%) housewife, 4 (8%)service holder, 2(4%) computer operator, 1(2%) doctor and 1(2%) were barber. In our study most common mode of presentation were chronic discharging sinuses 15(30%), beside this 12(24%) had multiple sinuses, 10(20%) had multiple pits,7(14%) had acute abscess and 6(12%) had unpleasant smell. Associated hirsutism were present in 30(60%) and absent in 20(40%) patients. One (2%) male patient had wound gap & discharge and six(12%) patients had flap edema. We have found no recurrence in follow up period.Conclusion : Pilonidal sinus is a notoriously recurrent disease, so treatment by this flap technique is the only hope of cure with lower morbidity.Journal of Surgical Sciences (2018) Vol. 22 (2) : 89-94